DEVELOPMENT OF A LOCALLY HANDMADE WATER TREATMENT PLANT FRAMEWORK: A CASE STUDY OF WATER FILTRATION TECHNIQUE IN KUNUKUNUMA COMMUNITY - Otuaro Ebierin Akpoebidimiyen and Igoma, Emughiphel Nelson (INTERNATIONAL JOURNAL OF PROGRESSIVE RESEARCH IN ENGINEERING MANAGEMENT AND SCIENCE (IJPREMS), 2025)
The need for a water treatment plant arises in a local community like Kunukunuma because of the high cost or financial involvement in executing a modern type of it. Therefore, the need for the locally handmade treatment plant framework emanated. The work involves the usage of floater boards in the construction of a cheap water treatment plant for household usage in Kunukunuma community. The floater board was cut into sizes to match the four stages of the filtration process. The stages start from the raw water container, flocculation, sedimentation and stop at the filter bed. Then from the filter bed, the clean water is taken via a container. Before the raw water was put into the raw water container, it was taken to a laboratory for microbial analysis tests and the result showed that it contained bacteria, thereby giving justification for the work. It is recommended that further testing should be conducted on the treated water to ascertain the cleanliness or purity of the water before drinking or usage.
Keywords: Development; Locally Handmade; Water; Treatment; Plant; Filtration.